2008
DOI: 10.1515/jpem.2008.21.9.847
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Glucoregulation in Childhood Obesity - Association with Insulin Resistance and Hyperinsulinemia

Abstract: Our data show that hyperinsulinemia can successfully compensate for insulin resistance in the majority of the obese children. Since IFG is less frequent than IGT there is a need for performing OGTT to demonstrate abnormality of glucoregulation in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Using fasting insulin alone yielded similar results as using HOMA-IR when relationships with cardiovascular risk factors were examined in our study. Previous studies have shown that hyperinsulinaemia is associated with cardiovascular risk factors1 and it can initially compensate well for insulin resistance in obese children2. Libman et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using fasting insulin alone yielded similar results as using HOMA-IR when relationships with cardiovascular risk factors were examined in our study. Previous studies have shown that hyperinsulinaemia is associated with cardiovascular risk factors1 and it can initially compensate well for insulin resistance in obese children2. Libman et al .…”
Section: Discussionmentioning
confidence: 99%
“…In obese children, hyperinsulinaemia can initially compensate well for insulin resistance2. However, chronic obesity may persistently impair insulin-mediated glucose metabolism3.…”
mentioning
confidence: 99%
“…Population-based data documented that the epidemic of obesity has been followed by an epidemic of type 2 diabetes mellitus and impaired glucose tolerance (IGT) as observed both in adulthood and childhood (14,15) . Obesity is associated with insulin resistance and systemic low-grade infl ammation even in childhood (16,17) .…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of an accurate diagnosis of MS is increasing and in this regard, fasting blood glucose levels, which are less sensitive for detecting insulin resistance and deterioration in glucose metabolism than serum insulin levels or oral glucose tolerance tests, may limit early diagnosis of the syndrome 6) . Obesity is associated with a high incidence of abnormal serum levels of glutamic pyruvic transaminase (GPT).…”
mentioning
confidence: 99%